Impact of union practices on labor relations in China: Institutional trust as a moderator - Li, Yuanling; Dai, Zhongliang; Hu, Xiao (Frontiers in Psychology, 2022)
The particularities of Chinese union practices in the private sector and their impacts on the labor relations climate have raised much controversy. This paper presents the findings of a study that analyzed data from 926 enterprises in Chongqing, China through the lens of institutional trust. The study was designed to examine the influence of union practice on labor relations climate at the enterprise level. Particular attention was paid to the possible moderator effect that both employee and management trust in unions had on the labor relations climate. We found that employee-union trust positively moderated the impact of union practice on the labor relations climate. However, if the management-union trust exceeded employee-union trust, the management-union trust weakened the moderator effect of the employee-union trust. In other words, the management-union trust negatively moderated employee-union trust.